Middle Miocene (Serravallian) rhodoliths and coralline algal debris in carbonate ramps (Betic Cordillera, S Spain) - Aguirre, Julio; Braga, Juan C. (Frontiers in Earth Science, 2022)
Serravallian (middle Miocene) coralline algal assemblages at the southern margin of the Guadalquivir Basin (southern Spain) occur as rhodoliths preserved in situ or very close to their growth habitats (autochthonous–parautochthonous assemblages) and also as reworked remains (allochthonous assemblages). The former assemblages consist of spherical rhodoliths built up by encrusting to warty plants and also of large fragments of branches, whereas the latter are mostly unrecognizable small fragments occurring in channeled packstone–grainstone beds. In both cases, the most abundant components are members of the order Hapalidiales (Mesophyllum roveretoi, Mesophyllum sp., Lithothamnion ramosissimum, and less frequently Phymatolithon group calcareum and Lithothamnion group corallioides). Laminar growths of Lithoporella minus and branches of Spongites group fruticulosus and Sporolithon sp. occur very rarely. There are also anecdotal records of Subterraniphyllum thomasii, extending its upper stratigraphic range up to the Serravallian in the western Tethys. The autochthonous–parautochthonous coralline algal assemblages formed in a middle ramp, at several tens of meters of water depth, as suggested by the dominance of Hapalidiales. The allochthonous assemblages represent fragments of coralline algae derived from the middle ramp and redeposited in deeper settings, most likely the outer ramp, due to storm-generated currents.